The Relationship between Pedagogical Competence and Work Motivation of Educators on the Performance of Public Elementary School Teachers, Gugus Dokter Wahidin Sudiro Husodo - Alben Ambarita; Intan Sahara (9 772338317006)
Abstract: The Relationship between Pedagogical Competence and Work Motivation of Educators on the Performance of Public Elementary School Teachers, Gugus Dokter Wahidin Sudiro Husodo. The problem in this study is the low performance of educators. This study aims to determine a positive and significant relationship between pedagogical competence of educators and teacher performance, work motivation with teacher performance, pedagogical competence of teachers and work motivation with teacher performance. This type of research is ex-post facto correlation with a population of 61 educators, sampling techniques using probability sampling techniques and obtained as many as 38 educators as research samples. The results showed that there was a positive and significant relationship between pedagogical competence of educators and work motivation with teacher performance, which was at the level of "High Enough".Keywords: teacher performance, pedagogical competence, work motivationDOI : 10.23960/jmmp .v8.i3.2020